2009
DOI: 10.4314/njps.v24i1.46372
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Of Artesunate, ACTs And Their Combinants On The Spermatic Parameters Of The Male Guinea-Pig

Abstract: Summary:In this study, the comparative effects of half, normal and double clinical doses of artesunate; artesunate/sulfadoxine/pyrimethamine; artesunate/amodiaquine and their combinants (sulfadoxine/pyrimethamine and amodiaquine) on the semen parameters-total sperm count, motility, morphology, debris and premature/primordial cell count of the male guinea-pig were investigated. The agents caused significant (p<0.05) decreases in total sperm count and sperm motility, with increases in abnormal sperm cells (morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…However, GSH and SOD were significantly decreased (p<0.05) in ACT treated group as compared with the positive control. This correlates with the findings of other researchers [30,31]. Reduced GSH level signifies the rate of cellular redox and non-enzymatic antioxidant state of cells in higher animals [32].…”
Section: Discussionsupporting
confidence: 91%
“…However, GSH and SOD were significantly decreased (p<0.05) in ACT treated group as compared with the positive control. This correlates with the findings of other researchers [30,31]. Reduced GSH level signifies the rate of cellular redox and non-enzymatic antioxidant state of cells in higher animals [32].…”
Section: Discussionsupporting
confidence: 91%
“…Administration of overdose of artemisinin caused a marked decrease in the epididymal sperm number, progressive sperm motility and viability, whereas sperm abnormalities increased without alteration in the testicular sperm number and daily sperm production in the treated rats. The reproductive toxicity of artemisinin derivatives in male guinea pig and rats has been reported (Raji et al ., ; Obianime & Aprioku, ). The observations from the spermiogram in the present study further revealed that artemisinin induced an epididymis specific effect on sperm characteristics without affecting the normal spermatogenesis by the testes.…”
Section: Discussionmentioning
confidence: 99%
“…Raji et al [7] showed that artemether, leads to a significant reduction in the sperm motility, viability, sperm count and serum testosterone levels in a dose-dependent manner in rats. ART has also been shown to cause a decrease in sperm motility in guinea pigs [8]. ART induces toxicity in female reproductive system.…”
Section: Introductionmentioning
confidence: 97%